Find solutions to your problems with the expert advice available on IDNLearn.com. Our Q&A platform is designed to provide quick and accurate answers to any questions you may have.
Sagot :
Volume is length*width*height
V = LWH
Height = H
Width = H-2
Length = H+5
V = H(H-2)(H+5) = 30
H(H2+3H-10)=30
H3+3H2-10H = 30
H3+3H2-10H-30 = 0
Per the rational roots theorem the roots of the
polynomial will be within the factors of the
constant , -30, divided by the coefficient of
the highest term, 1 from H3
The real roots must be within the factors of -30/1
or the factors of -30
Factors of -30 are ± {1, 2, 3, 5, 6, 10, 15, 30}
We will use synthetic division to determine the roots.
I first tried 1, -1, 2, -2, 3, and determined that -3 is
a root of the polynomial H3+3H2-10H-30.
This means that (H+3) is a factor ... Note that if
H=-3 then H+3 = 0
The synthetic division looks like this:
-3 | 1 3 -10 -30 the root and the coefficients
| -3 0 30
---------------------------
1 0 -10 0
Since the last sum is 0, there is no remainder.
That means that H=-3 is a root of the polynomial.
The other terms from right to left become the
constant and coefficients of the new polynomial
in ascending order ... LEFT to RIGHT
H3+3H2-10H-30 = (H+3)(H2+0H-10)
(H+3)(H2-10) = 0
Since H=-3 will not work for positive height we
need to look at:
H2-10 = 0
H2 = 10
H = ±√10
Again, discarding the negative
Height = √10 inches
Width = H-2 = -2 + √10 inches
Length = H+5 = 5 + √10 inches
V = LWH
Height = H
Width = H-2
Length = H+5
V = H(H-2)(H+5) = 30
H(H2+3H-10)=30
H3+3H2-10H = 30
H3+3H2-10H-30 = 0
Per the rational roots theorem the roots of the
polynomial will be within the factors of the
constant , -30, divided by the coefficient of
the highest term, 1 from H3
The real roots must be within the factors of -30/1
or the factors of -30
Factors of -30 are ± {1, 2, 3, 5, 6, 10, 15, 30}
We will use synthetic division to determine the roots.
I first tried 1, -1, 2, -2, 3, and determined that -3 is
a root of the polynomial H3+3H2-10H-30.
This means that (H+3) is a factor ... Note that if
H=-3 then H+3 = 0
The synthetic division looks like this:
-3 | 1 3 -10 -30 the root and the coefficients
| -3 0 30
---------------------------
1 0 -10 0
Since the last sum is 0, there is no remainder.
That means that H=-3 is a root of the polynomial.
The other terms from right to left become the
constant and coefficients of the new polynomial
in ascending order ... LEFT to RIGHT
H3+3H2-10H-30 = (H+3)(H2+0H-10)
(H+3)(H2-10) = 0
Since H=-3 will not work for positive height we
need to look at:
H2-10 = 0
H2 = 10
H = ±√10
Again, discarding the negative
Height = √10 inches
Width = H-2 = -2 + √10 inches
Length = H+5 = 5 + √10 inches
We value your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. Find clear and concise answers at IDNLearn.com. Thanks for stopping by, and come back for more dependable solutions.